2017
DOI: 10.5195/jmla.2017.222
|View full text |Cite
|
Sign up to set email alerts
|

Writing Together to Get AHEAD: an interprofessional boot camp to support scholarly writing in the health professions

Abstract: BackgroundWriting for publication is an integral skill for both sharing research findings and career advancement, yet many faculty lack expertise, support, and time to author scholarly publications. Health professions educators identified writing as an area in which a new educators’ academy could offer support.Case PresentationTo address this need, a writing task force was formed consisting of a librarian, a School of Medicine faculty member, and a School of Nursing faculty member. The task force launched two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…We also promoted the services and resources that exist through the Health Sciences Library to support nursing faculty in the scholarly writing process by having a research and education librarian, who is also the nursing liaison librarian, partner in teaching and facilitating the Scholarship Circle. As von Isenberg and colleagues note, librarians are supportive collaborators in the writing process since they already provide guidance on many aspects of the writing and publishing process, such as developing search strategies, conducting literature reviews, finding and selecting journals for publication, and using reference management tools [13]. Scholarship Circle participants consulted with the librarian during and after the course with requests for assistance with these aspects of writing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also promoted the services and resources that exist through the Health Sciences Library to support nursing faculty in the scholarly writing process by having a research and education librarian, who is also the nursing liaison librarian, partner in teaching and facilitating the Scholarship Circle. As von Isenberg and colleagues note, librarians are supportive collaborators in the writing process since they already provide guidance on many aspects of the writing and publishing process, such as developing search strategies, conducting literature reviews, finding and selecting journals for publication, and using reference management tools [13]. Scholarship Circle participants consulted with the librarian during and after the course with requests for assistance with these aspects of writing.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to encourage junior and nontenure-track nursing faculty to consider writing for publication and participate more fully in scholarly activities, the Health Sciences Library and the College of Nursing at the Ohio State University collaborated on developing and implementing an online professional development course in the summer of 2016 called the Scholarship Circle. The course also provided an opportunity to teach participants about human and material resources that were available to faculty who were writing for publication, including library resources and librarian services, based on a collaborative model used regularly by liaison librarians in health sciences libraries [1315]. This report describes the Scholarship Circle course, data collected from surveys, and results from a bibliographic analysis of participants’ publications.…”
Section: Introductionmentioning
confidence: 99%
“…7 Writing-support programmes provided the necessary skills, motivation, and encouragement. 7,14 A surprising observation in the present study was that it was the residents, not associate professors or full professors or fellows, who were mostly the ones declaring that they had no interest in writing (p = 0.037), although in our practice, residents are the cornerstones in health care and bear most of the workload.…”
Section: Discussionmentioning
confidence: 56%
“…2,4,36,39,49 Besides the dearth in outcomes and impact studies, our scoping review revealed additional gaps in the published research, suggesting the following opportunities for future investigation. First, our review revealed the expansion of the academy model beyond medical schools, serving interprofessional campuses 36,39,40,52 and other health professions schools. Thus, there are opportunities for comparative study Figure 3 Results of a scoping review of the literature on academies in health professions education organized by a logic model framework, including resources provided to academies, activities undertaken by academies, output (i.e., number of products, services, and participants), outcomes (i.e., changes brought about by engagement with an academy), and impact (i.e., broader effect on the organization at large).…”
Section: Discussionmentioning
confidence: 99%